Effect of Saccharina japonica Intake on Blood Pressure and Gut Microbiota Composition in Spontaneously Hypertensive Rats - Ayaka Harui; Saki Maruyama; Yukiko Segawa; Nobutaka Kurihara (Microorganisms, 2024)
It was reported that the consumption of Saccharina japonica (SJ) lowers blood pressure (BP) in hypertensive rats. Hypertension is related to gut microbiota, and hypertensive patients develop dysbiosis. It was reported that the intake of dietary fiber and polysaccharides contained in SJ changes gut microbiota and increases short-chain fatty acids (SCFAs). The present study examined the effect of BP lowering by SJ in spontaneously hypertensive rats (SHRs) and observed changes in gut microbiota composition and SCFAs concentration. Male SHRs and Wistar Kyoto rats (WKYs) were fed a diet containing 5% SJ or a control diet for six weeks. We measured systolic BP (SBP) weekly, as well as mean arterial BP (MAP), the 16S rRNA gene, and SCFAs in the cecal contents at the end of the period. As a result, the intake of SJ significantly decreased SBP and MAP in SHRs. As well, it significantly changed the microbial diversity by altering the gut microbiota composition. Particularly, it increased the abundance of Bacteroides acidifaciens, which may be associated with the antihypertensive effect of SJ. Thus, SJ intake suppressed the increase in BP and altered the gut microbiota composition, although it did not significantly change the SCFAs concentration in the cecal contents.